Synthesis of magnesium-based Janus micromotors capable of magnetic navigation and antibiotic drug incorporation. (17th April 2020) - Paryab, Amirhosein; Madaah Hosseini, Hamid Reza; Abedini, Fatemeh; Dabbagh, Ali
Abstract : Fe3 O4 superparamagnetic nanoparticles were used in magnesium based Janus micromotors for the first time and the bactericidal activity of the micromotors reached nearly 100%. Abstract : In the present study, bubble-driven magnesium-based micromotors were fabricated through a shading method, and the potential of magnetic guidance of magnesium-based Janus micro/nanomotors through functionalization with superparamagnetic iron oxide nanoparticles (SPIONs) was investigated for the first time. SPIONs had physical electrostatic attraction with the positively charged magnesium spheres due to negative charges on their surfaces. It was also found that upon applying a field gradient, the micromotors' velocity increased by 13% unlike other magnetically navigated spherical magnesium-based micromotors which only show a change in direction. In this work the cytotoxicity of the moving magnesium-based micromotors was investigated for the first time and their cell viability corresponding to 100 μg ml −1 was nearly 80%. Also, an antibacterial drug molecule was attached to the surfaces of the micromotors through direct conjugation. The drug attachment was confirmed by FTIR analysis and the drug loading capacity was also measured. The antibacterial activity of the moving micromotors reached nearly 100% in in vitro medium through drug conjugation. Furthermore, it was shown that their motile state was more bactericidal compared with their static state.